1994
DOI: 10.1007/bf01091228
|View full text |Cite
|
Sign up to set email alerts
|

Significance for humans of the nutrient contents of the dry fruit ofTetrapleura tetraptera

Abstract: The nutritional quality of the dry fruit of Tetrapleura tetraptera, a tropical deciduous forest tree with characteristic fruits, used as a spice, was assessed. The fruit shell, fruit pulp and seed contained varying amounts of nutrients such as protein, lipids and minerals, which were comparable and some were even higher than popular spices such as red pepper, onion, curry and ginger. The crude fibre content of the fruit shell was noteworthy and can be considered a good source of this nutritional factor. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 1 publication
1
21
2
Order By: Relevance
“…The high levels of Ca in this work-point to the fact that it is not enough to assess Nigerian food substances in isolation but is much better to analyze the composite meal of which they are a part. The level of Ca in this work is higher than that reported for any unprocessed Nigerian food substance (Aremu and Abara, 1992;Essien et al, 1992;Udosen, 1995). The Ca in each of these soup meals meets the recommended dietary allowance of 800 mg for both adults and children (Food and Nutrient Board, 1989).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The high levels of Ca in this work-point to the fact that it is not enough to assess Nigerian food substances in isolation but is much better to analyze the composite meal of which they are a part. The level of Ca in this work is higher than that reported for any unprocessed Nigerian food substance (Aremu and Abara, 1992;Essien et al, 1992;Udosen, 1995). The Ca in each of these soup meals meets the recommended dietary allowance of 800 mg for both adults and children (Food and Nutrient Board, 1989).…”
Section: Discussioncontrasting
confidence: 77%
“…Most Nigerian soup meals are made up of vegetables, oil, meat, fish, crayfish, oysters, salt, spices, and water, whose proximate analyses have been published (Eyo et al, 1983;Ifon and Umoh, 1987;Essien, 1987;Essien et al, 1992;Udosen and Ukpanah, 1993;Udosen, 1995). The published works are mainly of the raw forms of the foods (Ifon and Bassir, 1980;Essien et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…The pods are useds as a popular seasoning spice in Southeastern Nigeria (16,17,29), and the dried fruits are used in flavoring soups, particularly the traditional pepper soup, a delicacy consumed by mothers from the first day of delivery to prevent postpartum contractions, as a lactation aid (16,25), and for gastrointestinal disorders, especially stomach ulceration (24). Although much nutritional evaluation has been done on the dried fruits of T. tetraptera (3,17,29), reports on the chemical composition of the different sections of the fruit are scarce. The purpose of this study was to compare the nutrient, mineral, and phytochemical constituents of the three different sections of the T. tetraptera fruit, so that the therapeutic properties and its health benefits can be fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that the fleshly pulps of the plant contain sugars, tannins, small fraction of saponin, and amino acids (7,9). Other researchers have reported that its pod has been used as a good seasoning spice in the Southeastern part of Nigeria (3,13,14).…”
Section: Introductionmentioning
confidence: 97%
“…Although the analyses of proximate, mineral, protein, sugar, starch, and phytochemical analysis of the fruits, pulp, and the woody shell have been reported (3,6,14,26), little information regarding the content of total chlorophyll, chlorophyll a, chlorophyll b, β-carotene, lycopene, and fatty acid profile(s) of the seed is available. The aim of this study was to determine the total chlorophyll, chlorophyll a and b, total carotenoids, β-carotene, and fatty acids (essential fatty acids) so that the seed's cardiovascular therapeutic properties and the nutritional and pharmaceutical potentials to human health can be fully understood by consumers.…”
Section: Introductionmentioning
confidence: 99%